2021
DOI: 10.1029/2020jg005762
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Basal Melting of the Shirase Glacier Tongue on the CO2 System in Lützow‐Holm Bay, East Antarctica

Abstract: The ocean absorbs more than 25% of anthropogenic carbon dioxide (CO 2 ) emitted by human activities (Friedlingstein et al., 2019;Le Quéré et al., 2016). The Southern Ocean accounts for 40% of the anthropogenic CO 2 absorbed by the ocean, and it plays an important role in the global carbon cycle as a sink of anthropogenic CO 2 (Gruber et al., 2019;Sabine et al., 2004;Takahashi et al., 2009). However, the estimation of air-sea CO 2 exchange is limited to the open water area of the Southern Ocean. The air-sea CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 62 publications
3
20
1
Order By: Relevance
“…(2006) have shown that the decrease of pCO 2 due to biological uptake exceeded the increase of pCO 2 due to increases of temperature from 54°S to 60°S along 52°W in 2001. Close to the continental margin, the decrease of dissolved inorganic carbon (DIC) of seawater by meltwater from sea ice and glacial ice leads to a reduction of pCO 2 and enhancement of atmospheric CO 2 uptake (Bates et al., 2014; Kiuchi et al., 2021). The results of Bates et al.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…(2006) have shown that the decrease of pCO 2 due to biological uptake exceeded the increase of pCO 2 due to increases of temperature from 54°S to 60°S along 52°W in 2001. Close to the continental margin, the decrease of dissolved inorganic carbon (DIC) of seawater by meltwater from sea ice and glacial ice leads to a reduction of pCO 2 and enhancement of atmospheric CO 2 uptake (Bates et al., 2014; Kiuchi et al., 2021). The results of Bates et al.…”
Section: Introductionmentioning
confidence: 99%
“…(2014) and Kiuchi et al. (2021) likely contain a spatiotemporal measurement bias associated with the icescape because the icescape is expected to precondition the surface environment (Deppeler & Davidson, 2017). Understanding the carbon cycle in the Antarctic seasonal ice zone requires eliminating the regional specificity of the data and obtaining highly accurate and diverse data for carbonate chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations